GREASE GUN ПОВРЕДИ НА ШЕПАТА - Маргарита Пенева; Љиљана Дамевска; Виктор Станков; Ѓорѓе Џокиќ (Македонско лекарско друштво = Macedonian Medical Association, 2012)
Introduction. High pressure injection injuries of the hand are rare and occur in an average of 1 in 600 cases of hand trauma. Under the benign appearance of the injury at first sight, a future disability might be hidden. Morbidity is dependent mostly on the material injectted, followed by the amount of the injected fluid. The timely diagnosis and treatment are equally important factors since the risk for amputation increases as time increases with treatment delay. High pressure injection injuries of the hand are considered surgical emergency. Case report. A 46-year-old, right-hand dominant man, accidentally injured himself with a paint gun. He was admitted to the hospital more than 24 hours after the injury. At the moment of the clinical evaluation the finger was with compromised circulation. Under potentiated intravenous anesthesia with Tourniquet on 250mm/Hg decompressive incisions were performed and part of the nonviable tissue was removed. Despite all the effort the pathophysiology of the injury and the time passed between the injury and the treatment had played their roles. After few weeks of treatment the finger was in a condition in which the only solution of the problem was its amputation. After the amputation the patient managed to accomplish a very good rehabilitation of the hand. Conclusion. High pressure injection injuries of the hand despite all the measures taken have a high amputation rate. Thus, we can conclude that the most important issues are prevention, including protective equipment and a high level of precaution during work.
GREASE GUN INJURIES OF THE HAND
Keywords: injury; hand; high pressure